Calibration of the Lunar Radiometer for Intuitive Machines' S.P. Hopper - Hamm, Maximilian; Knollenberg, Jörg; Grott, Matthias; Ziese, Ramona; Robinson, M. S.; Mabe, K.; Pacher, T.; Martin, T.; Rauer, H (2024)
The Nova-C lander, build by Intuitive Machines as part of the NASA Commercial Lunar Payload Service (CLPS) program, will land near the lunar south pole providing the opportunity for in-situ investigations of volatile presence [6,7]. Nova-C will carry the S.P. Hopper to the Moon, which will in a sequence of short flights land within the Marston crater (informal name) PSR, carrying the radiometer LRAD, two cameras, and a neutron spectrometer (PLWS).